Electret film and laminated piezoelectric sheet
The electret film with specified properties addresses the issue of in-plane uniformity in large-area sensors by achieving high sensitivity and uniform piezoelectricity, preventing malfunctions in devices like large-screen touch panels and bed sensors.
Patent Information
- Application Number
- JP2023101868
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2025-01-09
AI Technical Summary
Conventional electret films used in large-area sensors, such as large-screen touch panel displays and bed sensors, suffer from insufficient in-plane uniformity of piezoelectricity, leading to variations in sensor output signal intensity and potential malfunctions due to higher sensitivity.
The electret film is designed with a piezoelectric constant d33 of 40 pC/N or more and a coefficient of variation of 0.5 or less, featuring a porosity of 0% to 50%, an average pore diameter of 1 μm or less, and an aspect ratio of 4.0 or less, utilizing a polyolefin resin, particularly polypropylene with β-crystal forming ability, to achieve uniform piezoelectricity.
The solution results in an electret film with high sensitivity and excellent in-plane piezoelectricity uniformity, ensuring stable sensor performance across large areas without signal intensity variations.
Smart Images

Figure 2025002005000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electret film and a laminated piezoelectric sheet using the electret film. [Background technology]
[0002] An electret is a material in which a part of a polymeric material or an inorganic material that does not easily conduct electricity is semi-permanently polarized by thermally or electrically treating the material. For example, porous electrets using porous resin films are known to exhibit excellent piezoelectric effects and are widely used in actuators, oscillators, sonars, vibration power generators, sensors, etc. In order to obtain an electret film with excellent piezoelectricity, it is necessary to polarize the film at a higher voltage during charge injection and to inject a larger amount of charge.
[0003] As an example of a porous electret, Patent Document 1 proposes a compressible polyolefin film using a microporous membrane that utilizes β crystals of a polypropylene-based resin. Polypropylene resin is a polymer with low polarity, and since it is difficult to localize electric charge in the intramolecular skeleton due to its chemical structure, it is not possible to obtain a high piezoelectric constant by itself. Therefore, a high piezoelectric constant is achieved by introducing air, which has a different dielectric constant, into the pores and trapping the electric charge. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-55114 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, with the development of flexible electronics, research is being conducted on foldable devices using electret films as pressure-sensitive materials. Electret films using microporous membranes can be manufactured in large areas at low cost, and are therefore attracting attention for use in foldable devices. However, when conventional electret films are used in large-area sensors such as large-screen touch panel displays or bed sensors, the in-plane uniformity of the piezoelectricity is insufficient, and the strength of the sensor output signal depends on the position within the plane, making them prone to malfunction. Since the higher the sensitivity of the sensor, the more likely it is that variations in signal strength will occur, there is a strong demand for a piezoelectric film that is both highly sensitive and has excellent in-plane uniformity of signal strength. Therefore, an object of the present invention is to provide an electret film having high piezoelectricity and excellent in-plane uniformity of the piezoelectricity, and a laminated piezoelectric sheet in which the electret film and an electrode are laminated. [Means for solving the problem]
[0006] As a result of intensive research aimed at solving the above problems, the inventors have discovered that by setting the absolute value of the piezoelectric constant and the coefficient of variation of the absolute value of the piezoelectric constant within a certain range, an electret film having high sensitivity and excellent uniformity in signal intensity can be produced, and have completed the present invention.
[0007] That is, the present invention relates to the following. [1] Piezoelectric constant d 33 The absolute value of is 40 pC / N or more, and the measurement area is 400 cm 2 The variation coefficient of the absolute value of the piezoelectric constant is 0.5 or less. [2] The electret film according to [1] above, which is a porous film. [3] The electret film according to the above [1] or [2], having a porosity of 0% or more and 50% or less. [4] The electret film according to [3] above, wherein the average pore size in the film thickness direction is 1 μm or less, and the average aspect ratio of the pores is 4.0 or less. [5] The electret film according to any one of the above [1] to [4], which contains a polyolefin resin as a main component. [6] The electret film according to the above [5], wherein the polyolefin resin is a polypropylene resin having a β-crystal generating ability of 70% or more. [7] The electret film according to any one of the above [1] to [6], having a thickness of 10 μm or more and 200 μm or less. [8] A laminated piezoelectric sheet comprising the electret film according to any one of the above [1] to [7] and an electrode laminated thereon. [9] The laminated piezoelectric sheet according to the above [8], further comprising a protective film laminated thereon.
[10] A sensor device using the laminated piezoelectric sheet described in [8] or [9] above. Effect of the Invention
[0008] According to the present invention, it is possible to provide an electret film having high piezoelectricity and excellent in-plane uniformity of piezoelectricity, and a laminated piezoelectric sheet in which the electret film and an electrode are laminated. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, the embodiments of the present invention will be described in detail. Note that the following description is an example (representative example) of the embodiment of the present invention, and the present invention is not limited to the contents thereof as long as it does not depart from the gist of the present invention.
[0010] In the present invention, when it is described as "x to y" (x and y are any numbers), unless otherwise specified, it includes the meaning of "greater than x and less than y", as well as "preferably greater than x" or "preferably smaller than y". In addition, when it is stated that the amount is "x or more" (where x is any number), it also means that the amount is "preferably greater than x" unless otherwise specified, and when it is stated that the amount is "y or less" (where y is any number), it also means that the amount is "preferably smaller than y" unless otherwise specified. Furthermore, "x and / or y (x and y are optional configurations)" means at least one of x and y, and means the following three cases: x only, y only, and x and y.
[0011] [Electret film] Electret films are broadly divided into permanent dipole types, which are polarized by the dipole orientation of the polymer itself, and porous membrane types, in which a porous polymer film is charged to trap electric charge inside the bubbles, creating polarization in each pore. The former has a dipole polarized at the molecular level, i.e., on the order of Å to nm, while the latter has a dipole size that depends on the size of the pores, and therefore generally has a dipole of nm to μm size, which is larger than that of the permanent dipole type electret film. Therefore, while the porous membrane type electret film has high piezoelectricity, it tends to have more variation in piezoelectricity than the permanent dipole type.
[0012] The electret film of the present invention is not particularly limited as long as it has piezoelectric properties, but it is preferably a porous film in order to further enhance the piezoelectric properties.Moreover, it is more preferable to use an electret film in which a porous film is charged.That is, it corresponds to the above-mentioned porous membrane type electret film. When the electret film is a porous film, the method of making the film porous is not particularly limited, but examples thereof include chemical or physical foaming and stretching. Among these, stretching is preferred because it provides a dense porous structure and is easy to control the shape of the pores.
[0013] The electret film of the present invention has a piezoelectric constant d 33 The absolute value of is 40 pC / N or more, and the measurement area is 400 cm 2The variation coefficient of the absolute value of the piezoelectric constant is 0.5 or less. In order to set the absolute value of the piezoelectric constant and the coefficient of variation of the absolute value of the piezoelectric constant within the specified range, methods such as optimizing the conditions for charging the film and adjusting the size, shape and porosity of the pores in the porous film can be used. More specifically, since the porous electret film holds electric charges at the interface between the pores and the resin, the larger the pore surface area, the more electric charges it can hold. That is, the smaller the pore size and the more the number of pores, the larger the pore surface area and the higher the piezoelectricity. In addition, the porous electret film exhibits piezoelectricity when the pores are compressed and deformed by pressure, changing the value of the dipole. Therefore, the smaller the pore size and the more uniform the size and shape of the pores, the smaller the variation in piezoelectricity.
[0014] <Piezoelectric constant d 33 > The piezoelectric constant of this film is d 33 The absolute value of the piezoelectric constant d is 40 pC / N or more. 33 If the absolute value of d is 40 pC / N or more, sufficient sensitivity can be obtained when used as a sensor. 33 The absolute value of is preferably 50 pC / N or more, more preferably 60 pC / N or more, and even more preferably 70 pC / N or more. In particular, 100 pC / N or more is more preferable, 130 pC / N or more is even more preferable, 150 pC / N or more is even more preferable, and 200 pC / N or more is particularly preferable. On the other hand, the piezoelectric constant d 33 The absolute value of the piezoelectric constant d is preferably 10,000 pC / N or less. 33 By keeping the absolute value of d below 10,000 pC / N, the risk of spark discharge when incorporated into a sensor or actuator can be reduced. 33 The absolute value of is more preferably 8000 pC / N or less, and further preferably 5000 pC / N or less. The piezoelectric constant is measured by the method described in the examples.
[0015] <Variation coefficient of piezoelectric constant> The electret film of the present invention has a measurement area of 400 cm 2 The coefficient of variation of the absolute value of the piezoelectric constant is 0.5 or less. When the coefficient of variation is 0.5 or less, the in-plane variation of the piezoelectricity of the electret film is small, and when used in a pressure sensor, for example, stable sensing can be realized despite the large area. From the above viewpoint, the coefficient of variation is preferably smaller, specifically, preferably 0.4 or less, more preferably 0.3 or less, and even more preferably 0.15 or less. On the other hand, the lower limit of the coefficient of variation is not particularly limited, but from the viewpoint of production costs, it may be, for example, 0.0001 or more, 0.001 or more, or even 0.01 or more, or even 0.02 or more.
[0016] <Porosity> As described above, the electret film of the present invention is preferably a porous film, and its porosity is preferably 0% or more and 50% or less. The porosity is a value indicating the ratio of the space portion of the electret film, and the higher the porosity, the higher the piezoelectric constant. From the above viewpoint, the porosity is 0% or more, preferably 5% or more, and more preferably 10% or more. On the other hand, the porosity of the electret film is preferably 50% or less. If the porosity is 50% or less, the piezoelectric film can have excellent pressure resistance. From the above viewpoints, the porosity is more preferably 40% or less, even more preferably 35% or less, particularly preferably 30% or less, and most preferably 25% or less.
[0017] (Method of measuring porosity) The actual mass W1 of the measurement sample is measured, and the mass W0 when the porosity is 0% is calculated based on the density of the resin composition constituting the electret film. The porosity is calculated from these values based on the following formula. Porosity (%)={(W0-W1) / W0}×100
[0018] (Average pore size) The average pore size of the pores in the film thickness direction is preferably 1 μm or less. When the average pore size is 1 μm or less, a film having excellent pressure sensitivity is easily obtained. From the above viewpoint, the average pore size of the pores in the film thickness direction is preferably 0.5 μm or less, and more preferably 0.1 μm or less. The standard deviation in the hole size distribution of the holes is preferably 0.05 μm or less, more preferably 0.04 μm or less, and even more preferably 0.03 μm or less. Meanwhile, the variation coefficient of the hole size is preferably 2.0 or less, more preferably 1.0 or less, and even more preferably 0.8 or less. By having such a hole size distribution, an electret film having uniform hole sizes and excellent positional stability of signal strength can be obtained.
[0019] (average aspect ratio of holes) The average aspect ratio of the pores of the electret film of the present invention is preferably 4.0 or less. When the average aspect ratio of the pores is 4.0 or less, the variation of the pores tends to be small, and as a result, it is easy to achieve a coefficient of variation of the absolute value of the piezoelectric constant of 0.5 or less. From the above viewpoint, the average aspect ratio of the pores is more preferably 3.8 or less, even more preferably 3.6 or less, and particularly preferably 3.4 or less. On the other hand, there is no particular restriction on the lower limit, so long as it is 1.0 or more. Moreover, the coefficient of variation in the distribution of the aspect ratio is preferably 3.0 or less, more preferably 2.5 or less, and even more preferably 2.0 or less. When the coefficient of variation in the distribution of the aspect ratio has such a value, an electret film having high piezoelectricity and excellent positional stability of signal strength can be obtained.
[0020] The average pore size in the thickness direction of the film and the average aspect ratio of the pores can be determined by observing the average pore size and aspect ratio in the thickness direction of 100 or more pores from a cross-sectional SEM image of the electret film of the present invention and calculating the average value.
[0021] <Thickness> The thickness of the electret film of the present invention is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more. On the other hand, the upper limit of the thickness of the electret film of the present invention is preferably 200 μm or less, more preferably 150 μm or less, even more preferably 100 μm or less, even more preferably 80 μm or less, and particularly preferably 50 μm or less. When the thickness is within the above range, an electret film having excellent handling properties and piezoelectricity can be obtained. In addition, if the thickness is 50 μm or less, the film becomes thin and physically flexible, so it is considered that the deformation amount of the pores becomes large when a certain pressure is applied. As a result, polarization change occurs easily, which is preferable in that an electret film with particularly high piezoelectricity can be obtained.
[0022] <Resin composition> The resin composition constituting the electret film of the present invention will be described below. The resin that is the main component of the resin composition is not particularly limited as long as it can achieve the effects of the present invention, and examples thereof include polyolefin resin, fluororesin, vinyl chloride resin, polystyrene resin, butadiene resin, polyester resin, and acrylic resin. Among these, polyolefin resin is preferably used because it has a small environmental load and is easy to perform charging treatment.
[0023] (Polyolefin resin) As described above, the electret film of the present invention preferably contains a polyolefin resin as a main component, and more preferably contains a polypropylene resin as a main component. When the electret film contains a polyolefin resin as a main component, the content of the polyolefin resin in the electret film is 50% by mass or more, preferably 70% by mass or more and 99.9999% by mass or less, more preferably 80% by mass or more and 99.999% by mass or less, and even more preferably 90% by mass or more and 99.99% by mass or less.
[0024] (Polypropylene resin) When the electret film is mainly composed of a polypropylene resin, the content of the polypropylene resin in the electret film is 50% by mass or more, preferably 70% by mass or more and 99.9999% by mass or less, more preferably 80% by mass or more and 99.999% by mass or less, and even more preferably 90% by mass or more and 99.99% by mass or less. Examples of polypropylene resins include homopolypropylene (propylene homopolymer), and random or block copolymers of propylene and α-olefins such as ethylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, or 1-decene. Among these, homopolypropylene is more preferably used from the viewpoint of mechanical strength.
[0025] Furthermore, the polypropylene resin preferably has an isotactic pentad fraction, which indicates stereoregularity, of 80% or more and 99% or less, more preferably 83% or more and 98% or less, and further preferably 85% or more and 97% or less. If the isotactic pentad fraction is 80% or more, the mechanical strength is good. On the other hand, the upper limit of the isotactic pentad fraction is set at the upper limit that can be obtained industrially at present, but this will not apply in the future if a resin with higher regularity is developed at the industrial level. The isotactic pentad fraction means a three-dimensional structure or a ratio thereof in which all five methyl groups, which are side chains, are located in the same direction relative to the main chain formed by carbon-carbon bonds composed of any five consecutive propylene units. The assignment of signals in the methyl group region is in accordance with A. Zambelli et al. (Macromol. 8, 687 (1975)).
[0026] Moreover, the polypropylene resin preferably has a Mw / Mn, which is a parameter indicating the molecular weight distribution, of 1.5 or more and 10.0 or less, more preferably 2.0 or more and 8.0 or less, and further preferably 2.0 or more and 6.0 or less. A smaller Mw / Mn ratio means a narrower molecular weight distribution, but by making the Mw / Mn ratio 1.5 or more, sufficient extrusion moldability is obtained and industrial mass production is possible, while by making the Mw / Mn ratio 10.0 or less, sufficient mechanical strength can be ensured. Mw / Mn is measured by GPC (gel per emission chromatography) method and expressed as a polystyrene equivalent value.
[0027] The melt flow rate (MFR) of the polypropylene resin is not particularly limited, but in general, the MFR is preferably 0.5 g / 10 min or more and 15 g / 10 min or less, and more preferably 1.0 g / 10 min or more and 10 g / 10 min or less. By setting the MFR to 0.5 g / 10 min or more, sufficient melt viscosity can be obtained during molding and high productivity can be ensured, while by setting the MFR to 15 g / 10 min or less, sufficient strength can be ensured. The MFR is measured in accordance with JIS K7210-1 (2014) at a temperature of 230°C and a load of 2.16 kg.
[0028] The method for producing the polypropylene resin is not particularly limited, and examples thereof include known polymerization methods using known polymerization catalysts, such as a polymerization method using a multi-site catalyst represented by a Ziegler-Natta catalyst or a single-site catalyst represented by a metallocene catalyst.
[0029] Examples of polypropylene-based resins that can be suitably used in the present invention include commercially available products such as those sold under the trade names "Novatec PP," "WINTEC," and "WAYMAX" (manufactured by Japan Polypropylene Corporation), "Versify," "Notio," and "Tafmer XR" (manufactured by Mitsui Chemicals, Inc.), "Zelas" and "Thermorun" (manufactured by Mitsubishi Chemical Corporation), "Sumitomo Noblen" and "Tafthren" (manufactured by Sumitomo Chemical Co., Ltd.), "Prime Polypro" and "Prime TPO" (manufactured by Prime Polymer Co., Ltd.), "Adflex," "Adsyl," and "HMS-PP (PF814)" (manufactured by SunAllomer Co., Ltd.), and "Inspire" (Dow Chemical Co., Ltd.).
[0030] <β crystal formation ability> The polypropylene resin is preferably a polypropylene resin having a β-crystal generating ability of 70% or more. A non-porous film made of a resin composition mainly composed of a polypropylene resin containing a large amount of β-crystals shows excellent piezoelectricity after charging treatment, but by stretching the film to form a porous structure, even better piezoelectricity can be obtained. The formation of a porous structure using β-crystals is advantageous for preparing a porous structure because the pores are formed during the process in which the β-crystals in the polypropylene resin are transformed into α-crystals during the stretching process, and the porous structure is dense and does not depend on the particle size or dispersion diameter, compared to the conventionally known pore formation by adding an inorganic filler or an incompatible organic substance. A film made porous by using β crystals has a dense porous structure and a large surface area of the pores, so that more charges are easily trapped during the charging process. Since a porous electret film exhibits piezoelectricity due to charges trapped at the interface between the pores and the matrix, a dense porous structure of the film tends to improve the piezoelectric properties. In addition, a dense porous structure makes the distance between the pores very short, and the trapped charges are easily fixed by the mutual Coulomb force. This makes it difficult for the trapped charges to be discharged, and the properties of the electret film are also less likely to deteriorate.
[0031] The β-crystal formation ability of the electret film of the present invention can be regarded as an index showing that the polypropylene resin in the non-porous membrane before stretching has formed β-crystals. If the polypropylene resin in the non-porous membrane before stretching has formed β-crystals, many fine and uniform pores are formed by subsequent stretching, so that excellent mechanical properties can be obtained, and excellent voltage resistance can be obtained by forming fine and uniform pores.
[0032] The presence or absence of the β-crystal forming ability of the electret film of the present invention is determined by performing differential thermal analysis of the electret film using a differential scanning calorimeter and determining whether or not a crystal melting peak temperature derived from the β-crystal of the polypropylene-based resin is detected. Specifically, a laminated porous film is heated from 40°C to 200°C at a heating rate of 10°C / min using a differential scanning calorimeter, held at that temperature for 1 minute, then cooled from 200°C to 40°C at a cooling rate of 10°C / min, held at that temperature for 1 minute, and then heated again from 40°C to 200°C at a heating rate of 10°C / min. If a crystal melting peak temperature (Tmβ) derived from β crystals of the polypropylene resin is detected during reheating, it is determined to have β crystal formation ability.
[0033] The presence or absence of the β-crystal forming ability can also be judged from the diffraction profile obtained by X-ray diffraction measurement of an electret film that has been subjected to a specific heat treatment. In detail, an electret film that has been heat-treated at 170 to 190°C, which is a temperature exceeding the crystal melting peak temperature of a polypropylene-based resin, and then slowly cooled to form and grow β-crystals is subjected to X-ray diffraction measurement, and if a diffraction peak derived from the (300) plane of the β-crystals of the polypropylene-based resin is detected in the range of 2θ=16.0° to 16.5°, it is judged that the film has the β-crystal forming ability. For details regarding the β-crystal structure of polypropylene resins and X-ray diffraction measurements, reference can be made to Macromol. Chem. 187, 643-652 (1986), Prog. Polym. Sci. Vol. 16, 361-404 (1991), Macromol. Symp. 89, 499-511 (1995), Macromol. Chem. 75, 134 (1964), and references cited therein.
[0034] The above-mentioned method of obtaining the β-crystal generating ability of the polypropylene resin includes a method of not adding a substance that promotes the generation of α-crystals of the polypropylene resin, a method of adding a polypropylene resin that has been treated to generate peroxide radicals as described in Japanese Patent No. 3739481, and a method of adding a β-crystal nucleating agent, but in the present invention, it is particularly preferable to add a β-crystal nucleating agent to obtain β-crystal activity. By adding a β-crystal nucleating agent, it is possible to more uniformly and efficiently promote the generation of β-crystals of the polypropylene resin, and to obtain an electret film having β-crystal generating ability.
[0035] The degree of the β-crystal formation ability can be quantified by measuring the β-crystal formation ability. The β-crystal formation ability of the electret film is preferably 70% or more, more preferably 80% or more, even more preferably 85% or more, and particularly preferably 90% or more. When the β-crystal generating ability is 70% or more, the laminated piezoelectric sheet can exhibit suitable piezoelectric properties. There is no particular upper limit to the β-crystal generating ability, but it is preferably 100% or less. The β-crystal forming ability is calculated by the following method.
[0036] (Method for measuring β-crystal formation ability) The DSC measurement of the electret film is performed by the following method. First, the temperature is raised from 40 ° C. to 200 ° C. at 10 ° C. / min in a nitrogen atmosphere, held for 1 minute, and then cooled to 40 ° C. at 10 ° C. / min. After holding for 1 minute, the melting peak observed when the temperature is raised again at 10 ° C. / min is determined as the melting peak of β crystals when the peak exists in the temperature range of 145 to 157 ° C., and the melting peak observed at 158 ° C. or higher is determined as the melting peak of α crystals. The heat of fusion of each is calculated from the area of the region surrounded by the baseline and the peak drawn based on the flat part on the high temperature side, and the heat of fusion of α crystals is ΔHα, and the heat of fusion of β crystals is ΔHβ, and calculated by the following formula. β crystal formation ability (%) = [ΔHβ / (ΔHα+ΔHβ)]×100
[0037] <β crystal nucleating agent> In order to obtain excellent piezoelectricity, the electret film of the present invention preferably contains a β-crystal nucleating agent. By containing the β-crystal nucleating agent, it is possible to impart β-crystal generating ability.
[0038] Examples of β-crystal nucleating agents include amide compounds, tetraoxaspiro compounds, quinacridones, iron oxides having nanoscale sizes, alkali or alkaline earth metal salts of carboxylic acids such as potassium 1,2-hydroxystearate, magnesium benzoate or magnesium succinate, and magnesium phthalate, aromatic sulfonic acid compounds such as sodium benzenesulfonate or sodium naphthalenesulfonate, di- or triesters of di- or tribasic carboxylic acids, phthalocyanine pigments such as phthalocyanine blue, two-component compounds consisting of component A, which is an organic dibasic acid, and component B, which is an oxide, hydroxide, or salt of a metal in Group 2 of the periodic table, and compositions consisting of a cyclic phosphorus compound and a magnesium compound. If necessary, two or more kinds of β-crystal nucleating agents from these may be mixed and used.
[0039] Among these β-crystal nucleating agents, amide compounds are preferred in terms of the piezoelectricity of the resulting piezoelectric film. Examples of amide compounds include N,N'-dicyclohexyl-2,6-naphthalenedicarboxyamide, N,N'-dicyclohexylterephthalamide, and N,N'-diphenylhexanediamide, among which N,N'-dicyclohexyl-2,6-naphthalenedicarboxyamide is preferred. Since amide compounds have highly polar amide groups, they can localize charges in the crystal structure, and are considered to have high piezoelectricity.
[0040] Compounds with high polarity such as amide compounds have poor dispersibility in polypropylene resins with low polarity due to electrostatic interactions, and are prone to aggregation. However, general β crystal nucleating agents have the property of dissolving in polypropylene resins at a certain temperature range. Due to this property, the β crystal nucleating agent is uniformly dispersed in the polypropylene resin, and crystals derived from the β crystal nucleating agent are easily precipitated uniformly. It is believed that this is why crystals of the amide compound with high polarity are uniformly dispersed in the polypropylene resin with low polarity, resulting in high piezoelectricity.
[0041] Specific examples of commercially available β-crystal nucleating agents include the β-crystal nucleating agent "N-Jester NU-100" manufactured by New Japan Chemical Co., Ltd., and specific examples of propylene-based resins to which a β-crystal nucleating agent has been added include the polypropylene "Bepol B-022SP" manufactured by Aristech, the polypropylene "Beta(β)-PP BE60-7032" manufactured by Borealis, and the polypropylene "BNX BETAPP-LN" manufactured by Mayzo.
[0042] The content of the β-crystal nucleating agent in the electret film of the present invention can be appropriately adjusted depending on the type of β-crystal nucleating agent or the composition of the polypropylene-based resin, and the like. However, it is preferably 0.0001 parts by mass or more and 5.0 parts by mass or less, more preferably 0.001 parts by mass or more and 3.0 parts by mass or less, and even more preferably 0.01 parts by mass or more and 1.0 parts by mass or less, relative to 100 parts by mass of the polypropylene-based resin. If the content of the β-crystal nucleating agent is 0.0001 parts by mass or more, the β-crystals of the polypropylene resin are sufficiently generated and grown during production, sufficient β-crystal generating ability can be ensured, and the piezoelectricity of the electret film becomes good. In addition, even when the film is stretched to form a porous film, sufficient β-crystal generating ability can be ensured, and an electret film having the desired piezoelectricity can be obtained by charging the film. On the other hand, if the amount is 5.0 parts by mass or less, this is economically advantageous and also preferred since bleeding of the β-crystal nucleating agent onto the film surface does not occur.
[0043] (Other ingredients) The resin composition according to the present invention may contain components other than the polypropylene resin and the β-crystal nucleating agent, as long as the effects of the present invention are not impaired. For example, resins other than polypropylene-based resins may be contained, and examples of such resins include polystyrene-based resins, polyvinyl chloride-based resins, polyvinylidene chloride-based resins, chlorinated polyethylene-based resins, polyester-based resins, polycarbonate-based resins, polyamide-based resins, polyacetal-based resins, acrylic-based resins, ethylene-vinyl acetate copolymers, polymethylpentene-based resins, polyvinyl alcohol-based resins, cyclic olefin-based resins, polylactic acid-based resins, polybutylene succinate-based resins, polyacrylonitrile-based resins, and polyethylene oxide. resins, cellulose-based resins, polyimide-based resins, polyurethane-based resins, polyphenylene sulfide-based resins, polyphenylene ether-based resins, polyvinyl acetal-based resins, polybutadiene-based resins, polybutene-based resins, polyamideimide-based resins, polyamide bismaleimide-based resins, polyarylate-based resins, polyetherimide-based resins, polyetheretherketone-based resins, polyetherketone-based resins, polyethersulfone-based resins, polyketone-based resins, polysulfone-based resins, aramid-based resins, and fluorine-based resins.
[0044] (Additives) The electret film of the present invention may contain additives to the extent that the properties of the film are not impaired. The additives include recycled resins generated from trimming losses such as edges, which are added for the purpose of improving and adjusting molding processability, productivity, and various physical properties of the electret film; inorganic particles such as silica, talc, kaolin, and calcium carbonate; pigments such as titanium oxide and carbon black; flame retardants, weather resistance stabilizers, heat resistance stabilizers, antistatic agents, melt viscosity improvers, crosslinking agents, lubricants, nucleating agents, plasticizers, antioxidants, antioxidants, light stabilizers, ultraviolet absorbers, neutralizing agents, antifogging agents, antiblocking agents, slip agents, and colorants.
[0045] [Method of manufacturing electret film] Hereinafter, a method for producing the electret film of the present invention will be described. However, the following description is an example of a method for producing the electret film of the present invention, and is not limited to the electret film produced by the production method described below.
[0046] The electret film of the present invention is preferably produced through a film-forming step, a stretching step, and a charging step. The film-forming step, the stretching step, and the charging step will be described below in order.
[0047] (Film forming process) In the film-forming process, a non-porous film-like material made of the material that constitutes the electret film is formed. In the film-forming process, the material that constitutes the electret film is not particularly limited as long as it is formed into a film by a known method, but for example, the resin composition (material resin) that constitutes the electret film is heated and melted to form a film, specifically, the T-die method, the inflation method, etc. are used to form the film, and among them, the T-die method is preferably used. In addition, from a practical standpoint, it is preferable to melt-extrude the material resin through a T-die and cast it using a cast roll (chill roll, cast drum, etc.).
[0048] The materials constituting the electret film may be kneaded in a kneading device and then formed into a film. The kneading device used when kneading is not particularly limited. For example, a known extruder such as a single screw extruder, a twin screw extruder, or a multi-screw extruder can be used. Depending on the equipment structure and necessity, the extruder may be provided with a vent port connected to a pressure reducer to remove moisture and low molecular weight substances.
[0049] When using a casting roll as described above, the film-like molten resin (resin composition) extruded from the T-die is extruded onto the casting roll, and is taken up while being in close contact with the rotating casting roll to form a film-like material. In order to make the film-like material adhere to the casting roll, a touch roll, an air knife, an electric adhesion device, or the like may be attached to the casting roll. In addition, when the molten resin (resin composition) is cooled and molded into a film, the temperature of the cast roll is preferably 100° C. or higher, more preferably 110° C. or higher, and even more preferably 120° C. or higher. In the present invention, since the porosity can also be increased by opening holes in the crystalline and amorphous parts of the polypropylene resin during the stretching process, it is preferable to set the temperature of the cast roll to 100° C. or higher to obtain a nonporous membrane with a high degree of crystallinity. The upper limit of the casting roll temperature is preferably 140° C. or less, more preferably 135° C. or less, and even more preferably 130° C. or less. By setting the casting roll temperature to 140° C. or less, peeling from the casting roll during film formation is easy.
[0050] In the obtained nonporous membrane, the thickness of the effective portion excluding both ends is preferably 20 μm or more and 800 μm or less, more preferably 30 μm or more, even more preferably 40 μm or more, even more preferably 50 μm or more, and more preferably 700 μm or less, even more preferably 600 μm or less, and even more preferably 500 μm or less. If the thickness of the nonporous membrane is 20 μm or more, breakage during stretching can be prevented, and if the thickness of the nonporous membrane is 800 μm or less, stretching of the nonporous membrane can be facilitated. The layer structure of the nonporous membrane material of the electret film of the present invention may be not only the above-mentioned single layer structure, but also a structure in which other layers are combined.
[0051] (Stretching process) The obtained nonporous membrane-like material may be directly charged, or may be stretched. By stretching the nonporous membrane-like material, the nonporous membrane-like material can be easily made into a porous film. In the stretching process, the nonporous membrane may be uniaxially stretched or biaxially stretched, with uniaxial stretching being preferred. The uniaxial stretching may be longitudinal uniaxial stretching or transverse uniaxial stretching. The biaxial stretching may be simultaneous biaxial stretching or sequential biaxial stretching. When sequential biaxial stretching is employed among these, it is relatively easy to control the porous structure and it is easy to balance with other physical properties such as mechanical strength and shrinkage rate. The stretching of the film in the machine direction (MD) is called "longitudinal stretching", and the stretching in the direction perpendicular to the machine direction (TD) is called "transverse stretching".
[0052] The stretching temperature must be appropriately selected depending on the composition of the resin composition used, the crystalline melting peak temperature, the crystallinity, etc., but the longitudinal stretching temperature is preferably 60°C or higher and 140°C or lower, more preferably 80°C or higher and 120°C or lower. A longitudinal stretching temperature of 140° C. or less is preferable because stretching can be performed without breakage at a temperature below the melting point of the polypropylene resin, which is the main component, whereas a longitudinal stretching temperature of 60° C. or more is preferable because breakage during stretching can be suppressed.
[0053] The transverse stretching temperature is preferably 90° C. or more and 160° C. or less, more preferably 100° C. or more and 150° C. or less. When the transverse stretching temperature is within the specified range, pores are sufficiently formed, the porosity can be increased, and sufficient piezoelectricity can be obtained. In the case of successive biaxial stretching, for example, the pores generated during longitudinal stretching are enlarged, so that the porosity of the porous layer can be increased, and sufficient piezoelectricity can be obtained. The temperatures described above are for uniaxial stretching or sequential biaxial stretching, but the stretching temperature for simultaneous biaxial stretching may be adjusted within the range of preferably 90°C or more and 160°C or less, more preferably 100°C or more and 150°C or less, from the above-mentioned viewpoint.
[0054] The stretching ratio may be selected arbitrarily according to the desired porosity, but the stretching ratio per uniaxial stretching is preferably 1.1 to 20 times, more preferably 1.5 to 18 times, even more preferably 4 to 16 times, and still more preferably 4 to 10 times. By setting the stretching ratio per uniaxial stretching to 1.1 times or more, whitening progresses and the stretching-induced porosity occurs sufficiently, while by setting the stretching ratio to 20 times or less, the porosity is suppressed and a porous film with excellent pressure resistance can be obtained. In the case of sequential biaxial stretching, by stretching at the stretch ratio specified above for each axis, voids generated during the previous stretching are not deformed during the subsequent stretching.
[0055] (Charging process) The electret film of the present invention can be obtained by subjecting the non-porous film obtained in the film-forming process or the porous film obtained through the stretching process to an electrification treatment. The electrification treatment may be continuous or batch-type. The electrodes used in the electrification treatment may be wire electrodes, roll electrodes, plate electrodes, etc., on the front and back of the film, and an electric field may be applied between the electrodes, or electrodes may be formed directly on the front and back of the film by coating or vapor deposition, and then an electric field may be applied. Among these methods, the method using a wire electrode or a plate electrode is preferred from the viewpoint of uniformity of the electric field in the film charging, and among these, the method using a wire electrode is particularly preferred from the viewpoint of excellent voltage application efficiency. The electric field to be applied is preferably 0.1 MV / m to 10 MV / m, more preferably 0.2 MV / m to 8 MV / m, and even more preferably 0.3 MV / m to 6 MV / m. By applying an electric field of 0.1 MV / m or more, excellent piezoelectricity can be obtained. By applying an electric field of 10 MV / m or less, the effect of reducing dielectric breakdown during charging processing is achieved.
[0056] Furthermore, the electret film of the present invention can be subjected to surface treatments such as corona treatment, plasma treatment, printing, coating, vapor deposition, and even perforation, as necessary, within the scope of the present invention. It is also possible to stack several electret films of the present invention depending on the application.
[0057] [Laminated piezoelectric sheet] The laminated piezoelectric sheet in which the above-mentioned electret film and electrodes are laminated also falls within the scope of the present invention. Furthermore, the laminated piezoelectric sheet in which a protective film is laminated also falls within the scope of the present invention.
[0058] <Electrode> The laminated piezoelectric sheet of the present invention has at least one electrode, and preferably has at least two layers of electrodes disposed so as to sandwich the electret film. The layer that becomes the electrode may be any material as long as it is conductive, and aluminum foil, copper foil, silver foil, gold foil, nickel foil, tin foil, carbon sheet, etc. are preferably used.
[0059] The thickness of the electrode is preferably from 2 μm to 100 μm, more preferably from 3 μm to 50 μm, and further preferably from 5 μm to 30 μm. When the thickness of the electrode is 2 μm or more, the electrode can exhibit conductive stability, while when the thickness of the electrode is 100 μm or less, the flexibility of the laminated piezoelectric sheet can be increased.
[0060] <Protective film> The laminated piezoelectric sheet of the present invention preferably has at least one protective film. The protective film is preferably a porous film. By having the protective film in the laminated piezoelectric sheet of the present invention, deterioration of the electret film due to moisture can be prevented. In order to enhance the water resistance of the present laminated piezoelectric sheet, the protective film is preferably provided so as to cover the electret film and the electrodes. In order to protect both the front and back surfaces of the electret film and the electrodes, it is more preferable that at least two protective films are provided in the present laminated piezoelectric sheet.
[0061] In addition, since the protective film of the present invention is a porous film, the pressure applied to the laminated piezoelectric sheet is easily dispersed, so that the force is easily transmitted to a wide range of the electret film, and the piezoelectric properties are improved. The method of making the protective film porous is not particularly limited, but examples thereof include chemical or physical foaming and porous formation by stretching. Among them, porous formation by stretching is preferred because a dense porous structure is obtained and the shape of the pores is easily controlled.
[0062] As the protective film, resin films such as polyester-based resin films, polyolefin-based resin films, acrylic-based resin films, polystyrene-based resin films, polycarbonate-based resin films, and fluorine-based resin films can be suitably used, and from the viewpoint of thermal adhesion, films in which hot melt resins are laminated onto these films can also be used. These films are also readily available as commercially available laminate films. In particular, it is preferable that the protective film is made of the same material as the electret film. Therefore, when the electret film is made of, for example, a polyolefin-based resin, it is preferable that the protective film is made of a polyolefin-based resin film. Also, when the electret film is made of, for example, a polypropylene-based resin, it is preferable that the protective film is made of a polypropylene-based resin film. If the protective film and the electret film are made of the same material, the amount of dimensional change due to temperature will be the same. Therefore, even if the laminated piezoelectric sheet is subjected to temperature changes through thermal processing or the like, wrinkles and warping are unlikely to occur.
[0063] Specifically, the protective film is preferably mainly composed of a polyolefin resin, more preferably a polypropylene resin. The details of the content in the protective film when the main component is a polyolefin resin or a polypropylene resin are the same as those described for the electret film. In particular, the protective film is preferably made of a resin composition mainly composed of a polypropylene resin containing a large amount of β crystals, and therefore preferably has the ability to generate β crystals, and more preferably contains a β crystal nucleating agent. Forming a porous structure using β crystals in the protective film is advantageous for preparing the porous structure. The physical properties and characteristics of the main component resin of the protective film may be the same as those of the electret film. Therefore, the details of the polypropylene-based resin used in the protective film are as described in the electret film. In addition, details of the protective film having β-crystal activity, such as the method for determining whether or not the protective film has β-crystal formation ability, the method for obtaining β-crystal formation ability, the value of β-crystal formation ability, the type and content of the β-crystal nucleating agent, etc., are the same as those explained for the electret film, and the explanation thereof will be omitted. Note that, when the protective film has a β-crystal formation ability as high as 80% or more, the porous structure becomes dense.
[0064] In addition, the protective film may contain various additives, such as heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, crystal nucleating agents, colorants, antistatic agents, hydrolysis inhibitors, lubricants, flame retardants, conductive agents, and elastomers, to the extent that the properties of the protective film are not impaired.
[0065] The porosity of the protective film of the present invention is preferably more than 0% and not more than 50%, more preferably 5% to 40%, even more preferably 10% to 30%, and even more preferably 15% or more. By making the porosity of the protective film greater than 0%, the pressure applied to the piezoelectric sheet is easily dispersed, so that the force is easily transmitted over a wide area of the electret film, resulting in good piezoelectric properties. In addition, by making the porosity of the protective film less than 50%, the impact resistance of the piezoelectric sheet is good.
[0066] The thickness of the protective film of the present invention is preferably from 1 μm to 100 μm, more preferably from 5 μm to 50 μm, even more preferably from 10 μm to 40 μm, and even more preferably from 20 μm to 30 μm. When the thickness of the protective film is 1 μm or more, the piezoelectric sheet can be sufficiently water-resistant, and when the thickness of the protective film is 100 μm or less, the pressure applied to the piezoelectric sheet can be easily transmitted to the electret film, and the flexibility of the piezoelectric sheet can be ensured.
[0067] <Method of manufacturing laminated piezoelectric sheet> The laminated piezoelectric sheet of the present invention can be obtained by laminating the electret film and protective film produced by the above-mentioned method with electrodes. The order of lamination is preferably, from the outside, the protective film, the electrodes, and the electret film. For example, in the case of a laminated structure in which a protective film, an electrode, an electret film, an electrode, and a protective film are provided in this order, two electrodes and a protective film may be bonded together using an adhesive, and then the two electrodes may be overlapped so that they face each other with the electret film in between, and the ends of the protective film may be heat-sealed to seal them.
[0068] In addition, the present laminated piezoelectric sheet may be formed into a bag shape by laminating the electret film, the electrodes, and the protective film, and then fusing the ends of the protective film. The method for fusing the ends is not particularly limited, and may be heat sealing or the like. When forming a bag-like structure, it is preferable to provide two layers of each of the electrode and the protective film. For example, it is preferable to laminate a protective film, an electrode, an electret film, an electrode, and a protective film in this order, and heat the ends of the protective films to heat seal them together to form a bag-like structure. When two protective films are used, the ends of the two protective films may be partially fused together in advance prior to the lamination. Furthermore, the ends of the protective film may be bonded together by a method other than heat fusion.
[0069] <Applications of electret film> The electret film of the present invention can be used, for example, as an actuator, an oscillator, a sonar, a vibration power generation, a sensor, etc. Although there is no particular limitation on the electret film, for example, by mounting a lead wire or forming an insulating film to form a piezoelectric element, the pressure acting on the piezoelectric film can be converted into a voltage, and the pressure acting on the piezoelectric film can be detected or electricity can be generated. Among these, it is preferable to use it as a sensor device.
[0070] [Sensor device] The laminated piezoelectric sheet of the present invention can be made into a sensor device by providing lead wires and mounting circuits. Since the present laminated piezoelectric sheet has excellent water resistance and piezoelectric properties, preferred sensor devices including the present laminated piezoelectric sheet include vibration power generators, water level gauges, acoustic detectors, mat sensors, robot hands, and the like. EXAMPLES
[0071] The electret film and laminated piezoelectric sheet of the present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited in any way. The evaluations and measurements in the examples were carried out by the methods shown below.
[0072] (Evaluation method) (1) Thickness The thickness of the electret film was measured at 10 random points using a 1 / 1000 mm dial gauge, and the average value was calculated.
[0073] (2) Porosity The electret film was cut into a size of 100 mm wide x 100 mm long to prepare a measurement sample. The actual mass W1 of the measurement sample was measured, and the mass W0 when the porosity was 0% was calculated based on the density of the resin composition. The porosity was calculated from these values based on the following formula. Porosity (%)={(W0-W1) / W0}×100
[0074] (3) β crystal formation ability The DSC measurement of the electret film was carried out by the method shown below. First, the temperature was raised from 40 ° C. to 200 ° C. at 10 ° C. / min under a nitrogen atmosphere, and then held for 1 minute, and then cooled to 40 ° C. at 10 ° C. / min. Regarding the melting peak observed when the temperature was raised again at 10 ° C. / min after holding for 1 minute, the melting peaks present in the temperature range of 145 to 157 ° C. were considered to be the melting peaks of β crystals, and the melting peaks observed at 158 ° C. or higher were considered to be the melting peaks of α crystals. The heat of fusion of each was calculated from the area of the region surrounded by the baseline and the peaks drawn based on the flat part on the high temperature side, and the heat of fusion of the α crystals was ΔHα, and the heat of fusion of the β crystals was ΔHβ, and calculated by the following formula. β crystal formation ability (%) = [ΔHβ / (ΔHα+ΔHβ)]×100
[0075] (4) Average pore size in the film thickness direction The electret film was cut parallel to the stretching direction to prepare a sample, and the cross section of the sample was observed with a scanning electron microscope (SEM). The analysis range was set to an arbitrary 26 μm × 19 μm range on the cross section of the sample. The pore diameter in the film thickness direction was obtained for all pores (approximately 1000 pores) confirmed within the analysis range, and the average value was calculated. In addition, the standard deviation was calculated from the measured values of the pore diameter in the film thickness direction, and the coefficient of variation was calculated from the following formula. Coefficient of variation = standard deviation / mean
[0076] (5) Average aspect ratio of voids The electret film was cut parallel to the stretching direction to prepare a sample, and the cross section of the sample was observed with a scanning electron microscope (SEM). The analysis range was set to an arbitrary 26 μm × 19 μm range on the cross section of the sample. The pore diameter in the film stretching direction was calculated for all pores (approximately 1000 pores) confirmed within the analysis range. The aspect ratio (pore size in the stretching direction / pore size in the thickness direction) was calculated from the average pore size in the stretching direction and the pore size in the thickness direction of the film, and the average value was calculated. The standard deviation was calculated from the aspect ratio measurements, and the coefficient of variation was calculated from the following formula. Coefficient of variation = standard deviation / mean
[0077] (6) Piezoelectric constant d 33 Absolute value of Cut the electret film to a size of 20 cm wide x 20 cm long, and measure the area of the film to 400 cm. 2 The sample was used for measurement. The piezoelectric constant d was measured using a piezometer manufactured by Reed Techno Co., Ltd. 33 The piezometer terminal was a flat plate with a diameter of 8 mm, and the clamp load was 0.4 N, the static load was 1.0 N, and the dynamic load was 1.3 N. Measurements were taken on a sample measuring 200 mm wide x 200 mm long at 9 points spaced 2 cm apart in the width direction and 9 points spaced 2 cm apart in the length direction, for a total of 81 points. The average absolute measurement values are shown in Table 1. The measurements were carried out in an environment of 23° C. temperature and 50% RH humidity.
[0078] (7) Coefficient of variation The piezoelectric constant d calculated above 33 The standard deviation was calculated from the 81 absolute values, and the coefficient of variation was calculated using the following formula. Coefficient of variation = standard deviation / mean
[0079] The materials used in the examples and comparative examples are as follows. (Polypropylene resin) A-1: Homopolypropylene (Novatec PP FY6HA, MFR: 2.4g / 10min [230℃, 2.16kg load], Mw / Mn=3.2, Japan Polypropylene Corporation) (β crystal nucleating agent) B-1: N,N'-dicyclohexyl-2,6-naphthalenedicarboxamide (NU-100, manufactured by New Japan Chemical Co., Ltd.) (Antioxidants) C-1: A 1:1 mixture of tris(2,4-di-t-butylphenyl)phosphite and tetrakis[3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionic acid]pentaerythritol (IRGANOX-B225, manufactured by BASF)
[0080] (Formation of porous film 1) 100 parts by mass of polypropylene resin (A-1), 0.2 parts by mass of β-crystal nucleating agent (B-1), and 0.1 parts by mass of antioxidant (C-1) were mixed and melt-extruded at 280°C using a twin-screw extruder to obtain a mixture 1 for electret film. The mixture 1 for electret film was put into an extruder connected to a T-die with a lip opening of 1 mm, and molded, and was guided to a cast roll to obtain a non-porous film with a thickness of 300 μm. Then, using a film tenter facility (manufactured by Kyoto Machine Co., Ltd.), the mixture was stretched 5 times in the transverse direction at a stretching temperature of 120°C to obtain a porous film with a thickness of 80 μm. The porosity of the obtained porous film was 18%, the β-crystal forming ability was 70%, and the average pore size in the film thickness direction was 0.07 μm, the standard deviation of the pore size was 0.04 μm, and the coefficient of variation was 0.6. The average aspect ratio of the pores (length in the stretching direction / length in the film thickness direction) was 3.5, and the standard deviation of the aspect ratio was 3.8, with a coefficient of variation of 1.1.
[0081] (Formation of porous film 2) The electret film mixture 1 was put into an extruder connected to a T-die with a lip opening of 1 mm, molded, and guided to a cast roll to obtain a non-porous film with a thickness of 100 μm. Then, the film was stretched 7 times in the transverse direction at a stretching temperature of 120° C. in a film tenter facility (manufactured by Kyoto Machine Co., Ltd.) to obtain a porous film 2 with a thickness of 20 μm. The porosity of the obtained porous film was 18%, the β-crystal formation ability was 70%, and the average pore size in the film thickness direction was 0.05 μm, the standard deviation of the pore size was 0.02 μm, and the coefficient of variation was 0.4. The average aspect ratio of the pores (length in the stretching direction / length in the film thickness direction) was 3.1, and the standard deviation of the aspect ratio was 5.2, with a coefficient of variation of 1.7.
[0082] Example 1 The porous film 1 was placed on a flat plate connected to earth. A voltage of -15 kV was applied to a wire electrode placed at a position 30 mm above the porous film, and the wire electrode was passed over the porous film at a moving speed of 40 mm / sec to charge the porous film, thereby producing an electret film.
[0083] (Examples 2 and 3) An electret film was prepared in the same manner as in Example 1, except that the charging treatment was performed under the conditions shown in Table 1 for the distance between the wire electrode and the porous film 1 (electrode distance), the applied voltage, and the moving speed of the wire electrode.
[0084] Example 4 The porous film 2 was placed on a flat plate connected to earth. A voltage of -10 kV was applied to a wire electrode placed at a position 30 mm above the porous film, and the wire electrode was passed over the porous film at a moving speed of 40 mm / sec to charge the porous film, thereby producing an electret film.
[0085] Comparative Example 1 An electret film was prepared in the same manner as in Example 1, except that the charging treatment was performed under the conditions shown in Table 1 for the distance between the wire electrode and the porous film 1 (electrode distance), the applied voltage, and the moving speed of the wire electrode.
[0086] Comparative Example 2 The porous film 1 was placed on a flat plate connected to earth. A voltage of −11 kV was applied for 5 seconds to a needle electrode placed at a position 30 mm above the porous film, and the porous film was charged to produce an electret film. The electret films produced in the examples and comparative examples were evaluated by the above-mentioned methods, and the results are shown in Table 1.
[0087] [Table 1]
[0088] The electret films of Examples 1 to 3 have a piezoelectric constant d 33 Absolute value and measurement area 400cm 2 The coefficient of variation of the absolute value of the piezoelectric constant in the above measurement was within a predetermined range, and the piezoelectric properties were high and the in-plane uniformity of the piezoelectric properties was excellent. Among them, Example 4 had particularly high piezoelectric properties and excellent in-plane uniformity of the piezoelectric properties. On the other hand, Comparative Example 1 had a high coefficient of variation, and the signal intensity varied greatly within the plane. Moreover, in Comparative Example 2 in which a needle electrode was used, the standard deviation and coefficient of variation were large, and the in-plane variation in signal intensity was large. [Industrial Applicability]
[0089] The electret film of the present invention has excellent in-plane uniformity of piezoelectricity, even though it has a large area. Therefore, when a laminated piezoelectric sheet manufactured using the electret film is applied to a large-area sensor such as a bed sensor, the laminated piezoelectric sheet has excellent in-plane uniformity of piezoelectricity, and the sensor output signal strength does not depend on the position in the plane, so no malfunction occurs. Therefore, even if the sensor is highly sensitive and has a large area, the piezoelectric film can have excellent in-plane uniformity of signal strength. Such products such as sensor devices are useful, and the technology of the present invention is a technology of high industrial value.
Claims
1. Piezoelectric constant d 33 The absolute value of is 40 pC / N or more, and the measurement area is 400 cm 2 The variation coefficient of the absolute value of the piezoelectric constant is 0.5 or less.
2. The electret film according to claim 1 , which is a porous film.
3. The electret film according to claim 2 , which has a porosity of 0% or more and 50% or less.
4. 4. The electret film according to claim 3, wherein the average pore size in the film thickness direction is 1 μm or less, and the average aspect ratio of the pores is 4.0 or less.
5. The electret film according to claim 1 , which contains a polyolefin resin as a main component.
6. The electret film according to claim 5 , wherein the polyolefin resin is a polypropylene resin having a β-crystal generating ability of 70% or more.
7. 2. The electret film according to claim 1, having a thickness of 10 μm or more and 200 μm or less.
8. A laminated piezoelectric sheet comprising the electret film according to any one of claims 1 to 7 and an electrode laminated thereon.
9. The laminated piezoelectric sheet according to claim 8 , further comprising a protective film laminated thereon.
10. A sensor device using the laminated piezoelectric sheet according to claim 8.
Citation Information
Patent Citations
Compressible polyolefin film, piezoelectric element, vibration element, and sensor
JP2017055114A